A light microscopic and ultrastructural examination of calcified dental tissues of horses: 2. Ultrastructural enamel findings - Kilic, S.; Dixon, P.M.; Kempson, S.A. (British Equine Veterinary Association, 1997)
Ultrastructural examinations defined 3 equine enamel types termed equine (Eq.) Types 1,2 and 3 enamel, according to the transverse appearances of their enamel prisms and the amount and appearance of their interprismatic enamel. Eq. Type 1 enamel contained alternating rows of oval shaped prisms and thick interprismatic enamel plates, and was found adjacent to the amelodentinal junction. Eq. Type 2 enamel consisted of circular, 'keyhole' to 'horseshoe' shaped prisms with little or no interprismatic enamel and was located adjacent to the amelocemental junction. Eq. Type 3 enamel was composed of rounded prisms surrounded by large amounts of interprismatic enamel and was inconsistently present in a thin layer at the amelodentinal and amelocemental junctions. Prism decussation was seen in the thickest peripheral enamel of the upper cheek teeth but was present throughout incisor enamel therefore making incisors highly resistant to cracking. Scanning electron microscopic examination showed enamel crystals to be cylindrical shaped on transverse section; however, on transmission electron microscopic examination these crystals had shapes, ranging from near oval to rectangular and formed small subunits, with crystals diverging from each other at various angles.
Keywords: Calcified dental tissue; Enamel; Horse; Ultrastructure